Tests for electric cables under fire conditions. Circuit integrity. Test method for fire with shock at a temperature of at least 830°C for cables of rated voltage up to and including 0, 6/1, 0 kV and with an overall diameter exceeding 20 mm Part 1, (5th September 2019) - British Standards Institution,
No abstract available